2022
DOI: 10.1111/tbed.14600
|View full text |Cite
|
Sign up to set email alerts
|

Serological screening in wild ruminants in Germany, 2021/2022: No evidence of SARS‐CoV‐2, bluetongue virus or pestivirus spread but high seroprevalences against Schmallenberg virus

Abstract: Wildlife animals may be susceptible to multiple infectious agents of public health or veterinary relevance, thereby potentially forming a reservoir that bears the constant risk of re‐introduction into the human or livestock population. Here, we serologically investigated 493 wild ruminant samples collected in the 2021/2022 hunting season in Germany for the presence of antibodies against the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and four viruses pathogenic to domestic ruminants, namely, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
4
10
0
Order By: Relevance
“…There is no evidence that spillover of SARS-CoV-2 from human to deer populations occurred in the studied territory. Our results align with other European countries’ reports on wild deer populations [ 26 , 27 , 28 ]. Comprehensive studies from the United Kingdom [ 26 ], Austria and Germany [ 28 ] showed no sign of SARS-CoV-2 in several deer species.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There is no evidence that spillover of SARS-CoV-2 from human to deer populations occurred in the studied territory. Our results align with other European countries’ reports on wild deer populations [ 26 , 27 , 28 ]. Comprehensive studies from the United Kingdom [ 26 ], Austria and Germany [ 28 ] showed no sign of SARS-CoV-2 in several deer species.…”
Section: Discussionsupporting
confidence: 93%
“…Recent European efforts have sought to determine whether other deer species can also act as reservoirs for the SARS-CoV-2 virus. Serological studies conducted in Germany, Austria and the United Kingdom found no evidence of spillover of SARS-CoV-2 to cervid species in these regions [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence that spillover of SARS-CoV-2 from human to deer populations occurred in the studied territory. Our results align with other European countries' reports onild deer populations [24][25][26]. Comprehensive studies from the United Kingdom, Austria and Germany showed no sign of SARS-CoV-2 in several deer species.…”
Section: Discussionsupporting
confidence: 91%
“…They are considered to be timid and avoid contact with humans. This may explain our and other groups results, where red deer were found to be negative for SARS-CoV-2 screening [24][25][26]. Although routes of white-tailed deer infection are unclear, deer social behaviour might be the factor facilitating the quick spread of the pathogen.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation